Outcome of ganglion impar block in chronic coccydynia - Butt, Muhammad Farooq; Bhat, Tanveer Ahmed; Lone, Zubair Ahmad; Gupta, Sanjeev; Ghani, Abdul (International Journal of Research in Orthopaedics, 2023)
Background: Chronic coccydynia is an annoying condition and is characterized by pain in the tail bone. Most cases are treated conservatively initially but failed conservative management calls for interventions of various type. One of the interventions in the armamentarium of the orthopaedic surgeon is a ganglion impar block. The present study aimed at assessing the outcome of ganglion impar block in chronic coccydynia. Methods: This prospective study of five years duration included 27 patients with chronic coccydynia with failed conservative treatment. Visual analogue score (VAS) and Oswestry disability index (ODI) were used to quantify pain and the improvement in symptoms. Minimum final follow-up was two years. Results: The mean VAS and ODI scores pre-injection were 5.98±1.86 and 52.13±2.13, respectively. The mean VAS and ODI scores at final follow-up were 2.47±1.65 and 23.59±2.34, respectively. The improvement in the above objective scores was found to be statistically significant with a p=0.00257 for VAS score and 0.00425 for ODI score. One patient developed syncope post-injection and one patient complained of superficial injection site pain which persisted for three weeks. No significant or major complication was encountered. Conclusions: Ganglion impar block appears to be a very impressive modality of treatment for chronic coccydynia in view of the simplicity, ease and reproducibility of the technique along with minimal complication rates. However, randomized control trials with large sample size are recommended.